Parenting Styles and Self-Esteem in Adolescent Cybervictims and Cyberaggressors: Self-Esteem as a Mediator Variable - Maite Garaigordobil; Raúl Navarro (MDPI AG, 2022)
Background: Family relationships and self-esteem are relevant variables into the understanding of cyberbullying. However, little is known about the mediating role of self-esteem in the connections between cyberbullying and parenting. The study had two goals: (1) to analyze the relation between being a cybervictim and/or cyberaggressor and self-esteem, parents' acceptance/coercion, and parenting styles and (2) to explore whether self-esteem is a mediator in the relationship between parents' acceptance/coercion and being a cybervictim/cyberaggressor. Method: The sample comprises 3026 Spanish adolescents (51.5% girls and 48.5% boys) aged 12-18 years (Mage = 14.39; SD = 1.69). The study has a cross-sectional design, retrospective ex-post with multiple measurements. Results: (1) cybervictims and cyberaggressors have low self-esteem, and their parents have a low level of involvement/acceptance and a high level of coercion/imposition towards their sons/daughters, (2) participants whose parents were authoritarian obtained significantly lower scores in self-esteem and higher scores in cybervictimization/cyberaggression, whereas those whose parents were indulgent obtained significantly higher scores in self-esteem and lower scores in cybervictimization/cyberaggression, and (3) it was found a mediation of self-esteem in the relationship between the involvement/acceptance of both parents and being a cybervictim, as well as between the father's coercion/imposition and being a cyberaggressor. Conclusion: An adequate level of self-esteem, high parental acceptance/involvement, and a reasonably low level of coercion/discipline as the parenting style can have very positive effects on the prevention of cyberbullying.